Evidence for glucocorticoid receptor transport on microtubules by dynein - Harrell, Jennifer M. (2004)
Rapid, ligand-dependent movement of glucocorticoid receptors (GR) from cytoplasm to the nucleus is hsp90-dependent, and much of the movement system has been defined. GR.hsp90 heterocomplexes isolated from cells contain one of several hsp90-binding immunophilins that link the complex to cytoplasmic dynein, a molecular motor that processes along microtubular tracks to the nucleus. The immunophilins link to dynein indirectly via the dynamitin component of the dynein-associated dynactin complex (Galigniana, M. D., Harrell, J. M., O'Hagen, H. M., Ljungman, M., and Pratt, W. B. (2004) J. Biol. Chem. 279, 22483-22489). Although it is known that rapid, hsp90-dependent GR movement requires intact microtubules, it has not been shown that the movement is dynein-dependent. Here, we show that overexpression of dynamitin, which blocks movement by dissociating the dynein motor from its cargo, inhibits ligand-dependent movement of the GR to the nucleus. We show that native GR.hsp90.immnunophilin complexes contain dynamitin as well as dynein and that GR heterocomplexes isolated from cytosol containing paclitaxel and GTP to stabilize microtubules also contain tubulin. The complete movement system, including the dynein motor complex and tubulin, can be assembled under cell-free conditions by incubating GR immune pellets with paclitaxel/GTP-stabilized cytosol prepared from GR(-) L cells. This is the first evidence that the movement of a steroid receptor is dynein-dependent, and it is the first isolation of a steroid receptor bound to the entire system that determines its retrograde movement.